Sources and Chemical Weathering Implications of Strontium and Hydrochemistry in an Inland Alpine Permafrost Basin - Huiling Zhou; Zongxing Li; Baijuan Zhang; Fa Du; Jian Xue (Geochemistry, Geophysics, Geosystems, 2024)
Abstract The hydrochemical characteristics of river water are influenced by a multitude of factors, reflecting the surrounding geographical environment. The Shaliu River, located in the northeastern Tibetan Plateau (TP), serves as a typical inland alpine permafrost watershed. In this study, we compiled data on dissolved strontium (Sr) concentration, 87Sr/86Sr isotopic, and hydrochemical profiles from the Shaliu River during the ablation period (May–October). Additionally, we gathered information on the Sr concentration and 87Sr/86Sr in the sediment of the river. The pattern of spatial heterogeneity in observed strontium (Sr) compositions can largely be attributed to lithological characteristics encountered at different locations along the river. The chemical components of Sr in the waters are derived from a combination of carbonate and silicate materials, with carbonates contributing between 69% and 81% and silicates contributing 19%–31%. The annual dissolved Sr flux is estimated to be 132 t/a. In addition to the influence of lithology and weathering processes, we propose that freeze‐thaw cycles within the permafrost layer may significantly affect the chemical mass flux in alpine permafrost watersheds because they generate substantial amounts of loose and easily erodible materials. Climate warming may further intensify the weathering processes in these watersheds, potentially leading to an increase in the Sr flux. This study is crucial for developing a comprehensive understanding of the geochemical composition of dissolved solutes in alpine permafrost regions, as well as for identifying the factors that regulate river water chemistry.